„Wróciłam na polską Warmię i Mazury”. Wspomnienia Marii Zientary-Malewskiej z 1945 roku - Lisowska, Kinga (Biuletyn Historii Wychowania, 2026)
Maria Zientara-Malewska was a social activist, organizer of education in Warmia and Masuria under German occupation and after 1945, a teacher and promoter of the culture of the Prussian lands and the author of many studies referring to the traditions of this region. She also left behind personal notes, letters and memories. Especially in the latter, she presents a picture of the social and educational situation in East Prussia in the post-Blebiscite period and after regaining independence in 1945. Attention is paid to the problems and social situation of the population of Warmia and Mazury and the shaping of education in the Board of Trustees of the Masurian School District in 1945. Memories were treated as a secondary source, subject to the method of collecting data in the form of searching archives. At the same time, the events described by the author are confronted with historical data, thus criticizing the source.